1998
DOI: 10.1002/macp.1998.021991107
|View full text |Cite
|
Sign up to set email alerts
|

Long chain branching in ethylene polymerization using constrained geometry metallocene catalyst

Abstract: SUMMARY We report an experimental investigation on long chain branching (LCB) in ethylene polymerization with the Dow Chemical's constrained geometry catalyst system, CGC-TflPFPBMMAO, using a continuous stirred-tank reactor (CSTR) at 140°C, 3.45 x lo3 kPa, and a mean residence time (5) of 4 min. The effects of the catalyst (CGC-Ti) and co-catalyst (TPFPB and MMAO) concentrations on the catalyst activity, polymer molecular weight, and shear thinning were systematically examined. The boron cocatalyst had a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…[73] Recently, however, Wang and co-workers [183] found that LCB had considerable effects on the nonisothermal crystallization of PE samples in the DSC study of long-chain branched PEs (LCBD up to 0.44C/1000 Cs) prepared by CSTR technique with CGC-Ti catalyst. [9] The crystallization enthalpy and the ultimate crystalline degree decreased with increasing LCBD. At relatively low cooling rates, a small amount of long-chain branches could promote crystal nucleation but reduce growth rate due to restraints of LCB on chain movement or diffusion.…”
Section: Differential Scanning Calorimeter (Dsc)mentioning
confidence: 96%
See 3 more Smart Citations
“…[73] Recently, however, Wang and co-workers [183] found that LCB had considerable effects on the nonisothermal crystallization of PE samples in the DSC study of long-chain branched PEs (LCBD up to 0.44C/1000 Cs) prepared by CSTR technique with CGC-Ti catalyst. [9] The crystallization enthalpy and the ultimate crystalline degree decreased with increasing LCBD. At relatively low cooling rates, a small amount of long-chain branches could promote crystal nucleation but reduce growth rate due to restraints of LCB on chain movement or diffusion.…”
Section: Differential Scanning Calorimeter (Dsc)mentioning
confidence: 96%
“…These values give an average LCBD of the whole polymer sample. [8] Wang et al used 13 C NMR to measure LCBD of PEs produced by CGC-Ti [9] and Cp 2 ZrCl 2 catalysts. [10] Figure 1 shows that the resonance peaks of α and β methylene, as well as methine carbons, could be found in the 13 C NMR spectrum of a PE sample produced by MMAO/Cp 2 ZrCl 2 due to the formation of LCBs.…”
Section: Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent advent of the single-site type metallocene technology provides copolymers with narrow MWD and composition distributions 11,12) . A new type of metallocene, called constrained geometry catalyst (CGC) 13,14) , offers ready incorporation of a -olefins and ethylene macromonomers generated via b -hydride elimination and/or transfer to monomer to synthesize branched polyolefins and LLDPEs [15][16][17] . Such branched polymers and LLDPE's have an excellent combination of good mechanical properties and processibilities 18) .…”
Section: Introductionmentioning
confidence: 99%